Perancangan APAR dan Hidran Halaman pada Gedung Laboratorium - Alfian Djafar; Kholiq Deliasgarin Radhyantho; Gad Gunawan; Ridhwan Haliq; Fajar Habib Syarifudin; Ersamada Sinaga (Faculty of Engineering, Universitas Serambi Mekkah, 2024)
Fire protection can increase occupational safety and security factors from fire hazards. Therefore, this research aims to design a fire protection system in an integrated laboratory building. The fire protection design is active fire protection, namely yard hydrants and fire extinguishers. This research uses engineering research methods. The standards used are NFPA 14, NFPA 24, Regulation of PER.04/MEN/1980 and SNI 03-1375-2000. Fire extinguishers are designed by determining the minimum number of extinguishers required and the type of extinguishers to be used. The yard hydrant design is carried out by determining the minimum number of yard hydrants required. Based on the research results, 22 fire extinguishers are required on the 1st floor, while 12 fire extinguishers are required on each of the 2nd and 3rd floors. Based on the fire class, the recommended APAR is dry chemical powder and CO2. The number of hydrants required is 9, the groundwater tank volume is 130 m3 and the obtained flow is 0.04 m3/s with a total head of 54,342 m. The appropriate pump specification is therefore the Ebara centrifugal pump type 150x125 FS4LA with a power of 54,342 kW.